Green Synthesis of Silver Nanoparticles Using Citrus sinensis Peels Assisted by Microwave Irradiation as a Contrast Agents for Computed Tomography Imaging - Fatikasari, Tanty; Nurhasanah, Iis; Khumaeni, Ali (Universitas Gadjah Mada, 2024)
Contrast agents are extensively used to enhance the quality of images in computed tomography (CT) scans for brain exams, vascular imaging, and full-body imaging. Recent data indicate that iodine-based contrast agents have brief durations of blood circulation and may lead to harmful toxicity effects. This study aims to produce silver nanoparticles using environmentally friendly synthesis techniques facilitated by microwaves. The characteristics of nanoparticles have been studied using UV-vis, FTIR, XRD, and TEM techniques. The TEM analysis reveals that the silver nanoparticle has an average diameter of 9 nm and exhibits a spherical shape. The contrast-to-noise ratio (CNR) values of silver nanoparticles at 100, 150, and 200 mg/L concentrations are 35.79, 48.16, and 74.66, respectively. In comparison, iodine exhibits CNR values of 28.57, 34.69, and 48.56 at the same concentrations. The CNR values for tube currents of 140, 160, and 180 mA are 37.83, 44.98, and 48.26, respectively. In contrast, the CNR values in silver nanoparticles are 63.64, 75.32, and 81.67. The results obtained from the different concentrations and tube currents clearly demonstrate that silver nanoparticles have a higher CNR than iopamidol. Hence, silver nanoparticles have significant potential as contrast agents.